2022
DOI: 10.1177/09610006221104809
|View full text |Cite
|
Sign up to set email alerts
|

Librarians’ competencies for implementing embedded librarianship in university libraries

Abstract: The present study examines the extent of academic librarians’ teaching, research, communication, and interpersonal skills; key competencies required for the successful implementation of embedded librarianship in Tanzania. A mixed research approach, integrating both qualitative and quantitative approaches, was deployed to guide the collection of data from 166 librarians and 6 directors. Whereas cross-section survey questionnaires were used to collect data from librarians from six university libraries. Semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 52 publications
1
23
1
Order By: Relevance
“…They can also participate in scholarly journal evaluation, develop bibliometric indicators and methodologies and evaluate science and research policy (de Jager et al ., 2016; Onyancha, 2018). The librarian's embedding in the research process is at its infancy stage in Africa (Machimbidza et al ., 2022; Mushi et al ., 2020a, b). There are limited services provided for research profiling, systematic and scoping reviews and research profiling (Shin, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…They can also participate in scholarly journal evaluation, develop bibliometric indicators and methodologies and evaluate science and research policy (de Jager et al ., 2016; Onyancha, 2018). The librarian's embedding in the research process is at its infancy stage in Africa (Machimbidza et al ., 2022; Mushi et al ., 2020a, b). There are limited services provided for research profiling, systematic and scoping reviews and research profiling (Shin, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are limited services provided for research profiling, systematic and scoping reviews and research profiling (Shin, 2021). Studies such as Mushi (2021), Mushi et al . (2022) revealed that there is low adoption of RDM services in Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations